Factors Associated with the Utilization of the Buku KIA at Puskesmas Pemulutan, Ogan Ilir Regency, 2025 - Era Mardia Sari; Siti Amallia; Helni Anggraini; Anur Rohmin; Nelly Mariyam; Meta Rosdiana (Jurnal Kesehatan : Jurnal Ilmiah Multi Sciences, 2026)
Abstract The Maternal and Child Health (MCH) Handbook is called “The Buku KIA” serves as a communication tool between healthcare providers, pregnant women, breastfeeding mothers, and families to monitor health during pregnancy, childbirth, the postpartum period, as well as child growth and development. This handbook functions not only as a medical record but also as an educational medium to improve mothers’ knowledge and awareness of the importance of healthy behaviors during pregnancy and child care. However, the low level of utilization and incomplete completion of the Buku KIA remains a concern, as inadequate documentation of maternal and child health information may reduce opportunities for complication prevention and timely health interventions. This study aimed to identify factors influencing the utilization of the the Buku KIA. This research employed a descriptive analytic design with a cross-sectional approach. The study population consisted of 80 pregnant women, with a sample of 25 respondents selected using accidental sampling. Data were analyzed using univariate analysis with frequency distributions and bivariate analysis using linear regression tests. The results showed that education level (p = 0.001), knowledge level (p = 0.0004), the role of healthcare providers (p = 0.021), family support (p = 0.027), and perception (p = 0.025) had a significant influence on the utilization of the the Buku KIA. In conclusion, education level, knowledge level, the role of healthcare providers, family support, and perception significantly influence the utilization of the Buku KIA. Keywords: Education, knowledge, role of healthcare providers, family support, utilization of the MCH Handbook (the Buku KIA)